(untitled) (Historia, 2021)
One of the major aspects of the South African government's policy of separate development was the forced removal of the Blacks. One of the communities forcibly removed was the Bakwena ba Mogopa from Mogopa to Pachsdraai in 1983-1984. A perception was created by the goverment that the Bakwena moved voluntary. The main objective of this article is thus to shed more light on the forced removal of this group and to confirm the hypothesis that their removal was not voluntary. This article deals with the origin and settlement patterns of the Bakwena ba Mogopa, the reasons for the forced removal, the execution of the removal process, attempts made by the Bakwena to resist and some consequences of the removals.